THE ROLE AND FUNCTIONS OF ARTIFICIAL INTELLIGENCE IN MODERN MEDICINE (KIUT Publication, 2025)
Today, the field of medicine has reached a point where it is unimaginable without artificial intelligence technologies. The application of AI in diagnostics, treatment, patient monitoring, mental health support, and the pharmaceutical sector enhances patient safety, recovery outcomes, and the efficiency of healthcare systems. Modern scientific studies from 2023–2025 highlight the significant role of artificial intelligence in medicine and its positive results.